2015
DOI: 10.1103/physrevb.91.094503
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of the normal-fluid turbulence in counterflowing superfluidHe4

Abstract: We describe a new technique, using thin lines of triplet-state He * 2 molecular tracers created by femtosecond-laser field-ionization of helium atoms, for visualizing the flow of the normal fluid in superfluid 4 He, together with its application to thermal counterflow in a channel. We show that, at relatively small velocities, where the superfluid is already turbulent, the flow of the normal fluid remains laminar, but with a distorted velocity profile, while at a higher velocity there is a transition to turbul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
109
3

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 101 publications
(121 citation statements)
references
References 34 publications
9
109
3
Order By: Relevance
“…For example, Marakov et al have observed the flow profiles of normal fluid in thermal counterflow in a square channel by following the motion of seeded metastable He * 2 molecules using a laser-induced fluorescence technique [35]. Figure 3 shows how the normal fluid profile changes as the heat flux is increased.…”
Section: Two-fluid Model and Thermal Counterflowmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, Marakov et al have observed the flow profiles of normal fluid in thermal counterflow in a square channel by following the motion of seeded metastable He * 2 molecules using a laser-induced fluorescence technique [35]. Figure 3 shows how the normal fluid profile changes as the heat flux is increased.…”
Section: Two-fluid Model and Thermal Counterflowmentioning
confidence: 99%
“…The visualization experiment of thermal counterflow by Marakov et al showed that the normal fluid velocity distribution becomes a Poiseuille profile, a tail-flattened profile, and a turbulent profile [35], as explained above. Recall that the Melotte-Barenghi assumption argued that the laminar normal flow corresponds to the T1 state of QT [20,27].…”
Section: Poiseuille and Tail-flattened Normal Flow In A Ductmentioning
confidence: 99%
See 3 more Smart Citations